Recalled and recorded bowel habits confirm early onset and high frequency of constipation in day-care nursery children - Borgo,Hilton Coimbra (2009)
CONTEXT: Mothers recall early-onset constipation in children attending gastroenterology clinics. OBJECTIVES: To study the bowel habit of young children in the community to determine, first, whether early-onset constipation is confirmed in this setting and, second, the agreement between recalled and recorded bowel habit. METHODS:Defecation data of 57 children aged 6.0-40.7 mo were obtained by maternal recall (questionnaire on predominant stool characteristics) and by record (1,934 defecations registered prospectively at home and in the nursery). The bowel habit was classified according to stool frequency and proportion of stool characteristics (soft, hard and/or runny). Two criteria were used to classify recorded data, since the cutoff point for hard stools to identify constipation is undefined in children: predominant criterion and adult criterion, respectively with >50% and >25% of stools with altered consistency. Bowel habit categories were: adequate, constipation, functional diarrhea and "other bowel habit". Nonparametric statistics, and the Kappa index for agreement between recalled and recorded bowel habit, were used. RESULTS: Constipation occurred in 17.5%, 10.5%, 19.3% of the children by recall, the predominant and the adult criteria, respectively. Constipation was the main recalled alteration, vs 12.3% "other bowel habit". Only one child classified as having functional diarrhea (by the adult criterion). Agreement between recalled and recorded bowel habit was fair for constipation, by the predominant and the adult criteria (K = 0.28 and 0.24, respectively), but only slight (K <0.16) for other bowel habit categories. Individual data, however, pointed to a better relationship between recalled constipation and the adult rather than the predominant criterion. CONCLUSIONS: Frequent early-onset constipation was confirmed. Fair agreement between recalled and recorded constipation by the two used criteria indicates that recalled data are quite reliable to detect constipation.